The Effectiveness of Using Wattpad to Improve Students’ Writing Skills and Critical Thinking Skills: A Phenomenolog-ical Approach - Suhaeni, Neni (Journal of Literature Language and Academic Studies, 2022)
Wattpad has become a popular application both for reading and writing stories. Since most Wattpad users are people in the age school, it can be used as an alternative medium to help the student to improve not only their writing skills but also stimulate their critical thinking. Based on the interview was conducted with 23 Wattpad active users by using qualitative descriptive research based on a phenomenological approach. The interview result shows that almost all of the participants agree that using Wattpad can improve not only their writing skills. They also realize that by reading a lot of stories, they can improve their critical thinking skills. Besides, they can get information and new knowledge related to writing by sharing their experience with the other user. Therefore, the purpose of this article is to find out the effectiveness of using Wattpad to improve students’ writing skills and critical thinking skills based on the phenomenological approach.